If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -4) + 5 = 6 Reorder the terms: 6(-4 + x) + 5 = 6 (-4 * 6 + x * 6) + 5 = 6 (-24 + 6x) + 5 = 6 Reorder the terms: -24 + 5 + 6x = 6 Combine like terms: -24 + 5 = -19 -19 + 6x = 6 Solving -19 + 6x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + 6x = 6 + 19 Combine like terms: -19 + 19 = 0 0 + 6x = 6 + 19 6x = 6 + 19 Combine like terms: 6 + 19 = 25 6x = 25 Divide each side by '6'. x = 4.166666667 Simplifying x = 4.166666667
| y=(x^2-1)(3x^2-5x+1) | | 2+8i=0 | | -1.2m=3.4m | | 2x+17=6x-7 | | 2x+11y=23 | | -1.2m=4 | | 5x+7y=98 | | x^2+3x-10=8 | | 180=(3x+10)+(4x-8) | | 3b-15=17-b | | 5(x+7)-8(x+9)=99 | | 0.3x-1.2=3.9x+1.8 | | 4x+28=20 | | 8.5-3j=-8j | | 2v^2-3x-9=0 | | 0.75-2=0.25 | | 4x+28=20# | | 5.6*30= | | 3d+6=4d | | 3x^2=18-3x | | -2(-7x-9)=-108 | | 0.2x+6.5=6.2 | | 1.6k-72=4k-30 | | A-22+4=-2 | | lny-ln(N-y)=kt+C | | -3x(4x+3)=0 | | 10x^2-9=-9x | | 3(-2x-8)=-54 | | 12h-5=-h-3+13h-2 | | 9-5t=0 | | 1.5w+21=17+1.5w | | y+(5-x)=7 |